The developmental psychology of music - Hargreaves, David J. (Cambridge Cambridge University Press, 1986)
This book sets out the psychological basis of musical development in children and adults. The study has two major objectives: to review the research findings, theories and methodologies relevant to the developmental study of music; and to offer a framework within which these can be organised so as to pave the way for future research. It describes the relationship between thinking and music, and discusses the relationship between thinking and music in pre-schoolers and schoolchildren in areas such as singing, aesthetic appreciation, rhythmic and melodic development, and the acquisition of harmony and tonality. The book describes the development of musical taste, and discusses the questions of musical creativity, and of the social psychology of musical taste and fashion. As a comprehensive study of the links between developmental psychology and music education, Hargreaves' work demonstrates the practical and theoretical importance of psychological research on the process underlying children's musical perception, cognition and performance.